PELATIHAN PEMBUATAN VIDEO PEMBELAJARAN DI TK ABA KANDANG PANJANG PEKALONGAN - Nur Baiti Nasution; Syita Fatih ‘Adna; Dewi Mardhiyana (LPPM Universitas Pekalongan, 2021)
During the era of pandemic of Covid 19 , all schools in Indonesia are forced to implement online learning including the kindergartens. The aim of this activity is to train the teacher of TK ABA Kandang Panjang so that they can create, edit and puvlish video for students learning. The videos are created using android smartphone and edited using Youcut app. Then, the videos are uploaded to Youtube channel of TK ABA Kandang Panjang. There were 3 stages of this activity. They are preparation, implementation, and evaluation. This activity was followed by 6 classroom teacher and the headmaster of the kindergarten. Looking at the evaluation result, it is known that teachers knowledge about creating and editing video using smartphones are increased. However, the Youtube channel has not been used optimally. Keywords: early years education, online learning, kindergarten, learning video